Predictors of outcome with medical therapy in patients with pleural infection treated with intra-pleural fibrinolytics - Davies, C; Kearney, S; Gleeson, F; Davies, R (1998)
In patients with pleural infection, the failure of medical treatment (drainage and antibiotics) results in the need for surgery and/or death. It would be clinically helpful to be able to predict this failure at the time of presentation. We examined clinical predictors of outcome with medical therapy in 85 consecutive, prospectively identified patients (55 male; 30 female) receiving 14F chest drainage, antibiotics and intra-pleural fibrinolytics for pleural infection. Indices recorded included age, the length of history prior to admission, delay in initiating antibiotic treatment, antibiotic choice, time to drainage of the effusion, blood and pleural fluid bacteriology, pleural fluid pH, lactate dehydrogenase (LDH), glucose and pleural fluid appearance (purulent/non-purulent) and, in a sub-set, maximum pleural thickness on CT scan (46 patients). Decisions about surgical referral were made before data analysis. The clinical features were compared in those where medical therapy failed (surgery and/or death) with those where it succeeded. There were 13 (15%) failures of medical therapy with 11 (13%) of patients requiring surgery. There were 4 deaths (2 following surgery). Frank pleural fluid purulence was more frequent in patients failing medical therapy (10/13 failures v 29/72 successes, p<0.02 chi-square) and the absence of purulence was a useful predictor of medical success, (predictive value 93%). The presence of frank purulence was not clinically useful in predicting medical treatment failure, (predictive value 26%). There was a trend towards positive blood culture predicting medical failure which was mostly due to an association with mortality (5/13 failures v 11/72 successes, p=0.05 chi-square) There were no clinically or statistically significant differences in any other end point. In particular there were no differences in symptom duration prior to admission, pleural fluid biochemistry or positive culture, age, delayed chest drainage, delay to antibiotic administration or CT assessed pleural thickness. Of the end points considered in this study, frank pleural fluid purulence was the only clinically useful predictor of outcome with medical therapy in pleural infection.